Hydrogeochemical analysis of groundwater quality during the pre- monsoon season of Manipur, India - Rakshita Chaudhary; Nisha Gaur; Mohit Yadav (Water Science)
The water quality index (WQI) and irrigational index for groundwater were studied in the northeastern section of the Manipur Valley in northeast India. Water samples were collected in 2022 during the pre-monsoon season. To compute the water quality index for drinking water, the basic chemical parameters of total hardness, pH, electrical conductivity, total dissolved solids, Calcium, Sodium, Iron, Magnesium, Manganese, Chlorine, and Hydrogen Carbonate were used. The assessment of bacteriological quality is also done, which is crucial for overall water quality evaluation, alongside physical and chemical analyze. For determining irrigation suitability, irrigational indices such as sodium absorption ratio, sodium percentage, and magnesium hazard were calculated. WQI, %Na+, Sodium Adsorption Ratio (SAR), magnesium hazard, permeability Index and total hardness indicate that most water samples are harmless for irrigation and drinking purpose. They have affirmative relationships indicating that these characteristics are interdependent. Approximately 25% of the Piedmont zone groundwater is found to be unfit for agricultural and drinking usage. The encrustation of gypsum, halite, and evaporation into the Disang shares accelerate the dissolution of ions in Piedmont water, resulting in quality degradation. According to Gibbs plots, Durov Scatter Plot, and Hill Piper Trilinear Diagram of water dominated the rock-weathering process, while hydrochemical facies progressed from the beginning to the intermediate stage of Chadha’s graphical representation illustrates the progression of hydrochemical processes in surface water. Therefore, proper integrated water resource management and development are required for effective water resource utilization, particularly around the Piedmont zone. In recent years, the quality of groundwater has caused a significant deal of alarm, and an increasing number of studies relating to it have been published. The geological, structural, and geomorphological features in the intermontane Imphal Valley in Manipur, India, were identified using SRTM DEM data by QGIS Software. This area has simple geology and structural elements, making it an appropriate site to evaluate the use of remote sensing and GIS tools in geological studies. To prevent a water crisis, groundwater resources must be managed sustainably. The current study also concentrated on a bibliometric examination of groundwater management and access to gauge the state of the field. A bibliometric examination of these papers may offer insight into current research and trends. We are the first to join Groundwater Quality Assessment with bibliometric analysis. This prediction, if taken into consideration strategically during the planning of preventive measures for groundwater quality can help to analyze future evaluation to a great extent.